Use of solid-supported 4-fluorophenyl 3-nitro-2-pyridinesulfenate in the construction of disulfide-linked hybrid molecules. Issue 36 (15th September 2020) - Cui, Yan; Taguchi, Akihiro; Kobayashi, Kiyotaka; Shida, Hayate; Takayama, Kentaro; Taniguchi, Atsuhiko; Hayashi, Yoshio
Abstract : A new solid-supported 4-fluorophenyl 3-nitro-2-pyridinesulfenate is useful for the efficient synthesis of a cyclic peptide and a disulfide-linked glycoconjugate. Abstract : To construct disulfide-linked hybrid molecules systematically and efficiently, we established a more practical solid-phase disulfide ligation (SPDSL) system with enhanced utility. The group Npys-OPh( p F) shows reactivity similar to that of Npys-Cl, but it is more stable. An efficient synthesis of the cyclic peptide oxytocin and a peptide–sugar conjugate was accomplished as models. These results indicate that the Npys-OPh( p F) resin functions as a common synthetic platform in SPDSL.